2018
DOI: 10.18203/2320-6012.ijrms20184884
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of CBNAAT in the diagnosis of extrapulmonary tuberculosis

Abstract: Background: Tuberculosis is still a major health problem worldwide. It is estimated that about one-third of the world's population is infected with mycobacterium tuberculosis. Whilepulmonary tuberculosis is most common presentation; extrapulmonary tuberculosis is also an important clinical problem. CBNAAT is cartridge based nucleic acid amplification test with a well-established role in the diagnosis of pulmonary tuberculosis (PTB). We determined the effectiveness of CBNAAT in the diagnosis of extrapulmonary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…In our study, there were 144 (29.5%) CBNAAT positive specimens that had shown negative results for Acid-fast bacilli (70% Sensitivity and 96.1% Negative predictive value). The findings were similar to the study done in Maharashtra which had shown that (8/25) 32% samples had been missed for TB diagnosis by AFB smear which was positive for CBNAAT [27].…”
Section: Resultssupporting
confidence: 89%
“…In our study, there were 144 (29.5%) CBNAAT positive specimens that had shown negative results for Acid-fast bacilli (70% Sensitivity and 96.1% Negative predictive value). The findings were similar to the study done in Maharashtra which had shown that (8/25) 32% samples had been missed for TB diagnosis by AFB smear which was positive for CBNAAT [27].…”
Section: Resultssupporting
confidence: 89%
“…AFB smear hasn't proved to be much useful in diagnosing EPTB. 3 For several decades smear microscopy and conventional culture techniques have been the mainstay of diagnostic testing for pulmonary tuberculosis. While smear microscopy has poor sensitivity and issues related to quality control, conventional solid culture techniques have the limitation of long turnaround time of several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Raizada et al, that covered a population of 8.8 million across 18 sub-district level tuberculosis units (TU) in India, Overall 28% TB cases were bacteriologically confirmed, of which 27.6% TB cases were detected on CBNAAT against the smear positivity rate of 12.9%. 14 15 Similarly in a study carried out at Hydrabad India, for pulmonary samples the sensitivity and specificity of CBNAAT samples were 79.2% and 89.5% respectively while that for sputum smear negative were 41.5% and 98.2% respectively. For extra-pulmonary samples ,the sensitivity and specificity of CBNAAT samples were 85.7% and 93.5% respectively while that for smear negative were 60.7% and 100% respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Authors assumed that the specificity of Xpert is high, as every study performed to date and meta-analysis has indicated consistently high specificity of 99%. 15 Therefore, although there is no culture confirmation for comparison, this study was not an evaluation of diagnostic accuracy, which has been comprehensively reported elsewhere in other studies. 13,14 It can be reasonably assumed that the cases studied in our study are genuine, and the rate of false positive diagnosis is unlikely to exceed that of culture.…”
Section: Resultsmentioning
confidence: 99%